Analisis Pelaksanaan Kebijakan Mutu Pendidikan di SMP Negeri 1 Bukittinggi - Almasri Almasri; Marjoni Imamora; Demina Demina; Annisaul Khairat (Pendidikan Agama Islam STIT Palapa Nusantara, 2023)
The aims of this study were (1) to find out the implementation of quality policy in schools, (2) to prevent inhibiting and supporting factors for the implementation of quality policy in schools, (3) solutions to deal with obstacles to implementing quality policy in SMPN 1 Bukittinggi. This type of research is field research using descriptive qualitative methods. Data collection techniques used are interviews and documentation. The research results show that. 1) analysis of the quality of education policy at SMPN 1 Bukittinggi seen from the very good input elements, one of which is the selection process for prospective students and teachers, in terms of the process there is continuous coaching for each teacher and employee in the form of training and coaching, in terms of output there is an assessment standard so that graduates have high academic and non-academic achievements. 2) The inhibiting factors for quality include: there are still teachers and education staff who do not understand the importance of quality/quality by educational institutions besides that, there are parties who are against school policies, giving rise to jealousy and differences of opinion. Supporting factors include: the availability of qualified educators and education personnel. Availability of facilities and infrastructure above the minimum standard. Availability of a conducive learning process environment, discipline and other supporting factors. 3) Solutions for overcoming obstacles to school quality policies are through dissemination of school policies, optimizing compliance with National Education Standards, strengthening commitment in achieving the goals of educational institutions. An important finding in this study is that SMPN 1 Bukittinggi can be said to be a quality school. This is because the three components of education quality have been fulfilled, namely: input, process and output as a whole.